Competence-Based Education Pedagogy and Its Infusion into Primary School Learning Activities: Experiences from Teachers in A Selected Cluster in Eswatini - Cyprian, Dlamini; Chikuvadze, Pinias; Young, Mudavanhu; Daimond, Dziva; Claretah, Makuvire (Journal of Educational Research and Practice, 2025)
This study sought to explore how Competency-Based Education (CBE) pedagogy was implemented in the selected primary schools and to understand teachers' experiences with this pedagogical approach. The study was rooted in a mixed research method approach. For this study, 24 respondents were selected through a stratified random technique. Data was collected through an interview and semi-structured questionnaire. In quantitative data, percentages were used, and qualitative data was analyzed according to emerging themes. This created the platform for quantitative and qualitative data to corroborate each other. The analyzed and interpreted data revealed that seminars, peer tutoring, and workshops were commonly used to prepare teachers to integrate CBE pedagogy into all learning activities. The results showed that student-centered methods, such as problem-solving, inquiry-based, project-based, and design-based learning, were central to CBE pedagogy's integration into primary school learning activities. Integrating CBE pedagogy in primary school teaching and learning fosters flexible, personalized learning emphasizing skills development. Based on the results, the teachers in the selected primary school's cluster facilitated the infusion of CBE pedagogy into learning activities. Continuous teachers' professional development should enhance their competencies in implementing CBE pedagogy into learning activities.